Characteristics of sports brand content on social media and their effects on consumers - Liu, Yue (Frontiers in Sports and Active Living, 2025)
IntroductionWith the rise of short-video platforms, social media—especially TikTok—is profoundly transforming the marketing model of the sports industry. These platforms provide brands with targeted consumer engagement channels that enhance communication efficiency and drive digitalization, creating a need to understand the specific mechanisms through which content influences consumer behavior.MethodsThis study empirically investigated these mechanisms by surveying 1,400 adult consumers in mainland China who have purchased sports products on TikTok. Data were collected using validated scales for brand content characteristics (informativeness, entertainment, interactivity, authenticity), brand attitude, brand loyalty, and purchase intention. The proposed relationships were analyzed using structural equation modeling with SPSS 28.0 and AMOS 28.0.ResultsThe findings reveal that all four content characteristics significantly impact purchase intention. Notably, the effects of informativeness and interactivity were found to be comparable in magnitude. Furthermore, brand attitude and brand loyalty served as significant mediators in the relationship between content characteristics and purchase intention. Crucially, the indirect effects through these psychological mediators surpassed the direct influence of the content itself.DiscussionThe results underscore that the primary value of TikTok content marketing lies not in direct persuasion but in building brand assets. We conclude that sports brands can optimize their digital strategy by prioritizing content that delivers valuable information and fosters active interaction, thereby directly and indirectly enhancing purchase intention through the cultivation of positive brand attitude and steadfast brand loyalty.